Pengukuran Jarak Terbatas Menggunakan Kombinasi Sensor Berat Dan Pegas Tekan Dengan Tampilan Pada Perangkat Smartphone - Aprillia, Ajeng Murtirani, Dedi Ary Prasetya S.T, M.Eng (2017)
Penggunaan alat ukur analog memiliki banyak kelemahan dibandingkan penggunaan alat ukur digital. Beberapa keunggulan alat ukur digital antara lain tampilan bagus. Alat ukur digital yang menggunakan sensor load cell juga dapat digunakan sebagai alat ukur jarak untuk menggantikan jangka sorong yang fungsinya sebagai alat ukur digital, hasil pengukuran jarak tersebut dapat dilihat pada LCD 16x2 dan smartphone. Pengukuran jarak tersebut menggunakan 2 jenis pegas yaitu pegas A yang mempunyai diameter kawat 0.8 mm, diameter pegas 13 mm, panjang 119 mm, dan konstanta 80,752 N/m. Pegas B mempunyai diameter kawat 1,0mm, diameter pegas 14mm, panjang 119mm, dan konstanta 147,490 N/m. Pengukuran jarak pegas A menggunakan beban 60,76 -2625,42 Newton mengahasilkan jarak 0,8 - 34 mm dan pegas B menggunakan beban 59,78-1422,96 Newton mennghasilkan jarak 0,55-11,85 mm. Perubahan jarak tersebut dengan memberikan The use of analog measuring instrument has many disadvantages compared to the use of digital measuring instrument. Some of the benefits of a digital measuring instrument are more nice view. Digital measuring instrument that uses a load cell sensor can also be used as a distance measuring instrument to replace the calliper that functions as a digital measuring instrument, the distance measurement results can be viewed on the LCD 16x2 and smartphones. The distance measurement using two types of springs that are spring A having a wire diameter of 0,8 mm, 13 mm spring diameter, length 119 mm, and the constant 80,752 N/m. Spring B has a wire diameter of 1,0mm, 14mm spring diameter, length 119mm, and the constant 147,490 N/m. Distance spring measurements using 60,76 -2625,42 Newton load produces range 0,8 - 34 mm and the springs B using a load of 59,78-1422,96 Newton produces range 0,55-11,85 mm. The distance changes with adding burden at the top of the spring placed on the load cell will get the value of the weight, measurement height and digital height. Spring A compared difference between the height measurment and height digitally getting an average of 0,323 mm, and the spring B get an average of 0,033 mm difference. The results of the difference between digital height and manual height spring A compared with spring B which has a smaller result is spring B. The testing data can be concluded with spring A, with small constant then the distance gained is longer and spring B using greater constant, the distances obtained is shorter.